PENGEMBANGAN PUSAT KOTA DENPASAR SEBAGAI ‘HERITAGE TOURISM’ - Suarmana, I Wayan Restu; Ardika, I Wayan; Darma Putra, I Nyoman (Jurnal Master Pariwisata (JUMPA); Volume 04, Nomor 01, Juli 2017, 2017)
Heritage tourism is a tourism that utilizes heritage or historical heritage as tourist attractions. The existence of heritage for Denpasar is regarded as the theme of tourism development in the future. Nowadays, the existence of heritage sites are more neglected and abandoned due to the modernization effect. In fact, if it is managed and organized properly, it will contribute many positive benefits. This research analyses two research problems focusing on the existing condition of Denpasar city as heritage tourism. Besides, it is by planning the heritage tourism model in Denpasar city. The method used in this research is descriptive qualitative. The informants were chosen by base informants and snowball technique. Concepts used in discussing this research are the development model of tourism concept, urban tourism concept, and the heritage tourism concept. The theories used for this research is destination area life cycle. According to the results of the discussion, it can be concluded that, the existence of cultural heritage in Denpasar city is started to be explored and improved along with the objective and benefits owned by each heritage. The development model of heritage tourism which is now planned in Denpasar city comprises daily activity heritage tour.